The Influence of Work Motivation, Work Discipline and Work Environment on Employee Performance in Tourism Businesses for Lodging Services - Dewi Yuliati Indah; Ossy Vina Sonia (Innovation Business Management and Accounting Journal, 2024)
This study is to determine the effect of motivation, work discipline and work environment on employee performance at Grand Metro Hotel Tasikmalaya. This study uses descriptive and verification methods, the sample size is 48 employees. The data collection techniques used were observation, interviews and questionnaires. The data analysis methods used are validity and reliability tests, multiple linear regression analysis, multiple correlation analysis, and the coefficient of determination. Based on the results of the analysis, simultaneously the effect of motivation, work discipline and work environment on employee performance is positive and significant. While the results of the analysis partially, the motivation variable has the most dominant influence value compared to the discipline and work environment variables.